Descriptiveness of vaginal secretions pH in the vaginal microbiota assessment in pregnant women - V. F. Nagornaya; T. Ya. Moskalenko; A. A. Gritsenko (Kazimierz Wielki University, 2016)
Nagornaya V. F., Moskalenko T. Ya., Gritsenko A. A. Descriptiveness of vaginal secretions pH in the vaginal microbiota assessment in pregnant women. Journal of Education, Health and Sport. 2016;6(7):67-74. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57113 http://ojs.ukw.edu.pl/index.php/johs/article/view/3659       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016.     UDC 618.3-06: 618.15-022.7] -07-085   DESCRIPTIVENESS OF VAGINAL SECRETIONS pH IN THE VAGINAL MICROBIOTA ASSESSMENT IN PREGNANT WOMEN   V. F. Nagornaya1, T. Ya. Moskalenko1, 2, A. A. Gritsenko2   1Odessa National Medical University, Department of Obstetrics and Gynecology №1; 2 KU maternity hospital №7, Odessa           Summary 143 pregnant and 20 non-pregnant women have been examined. The objective: to determine the information content of  the vaginal fluid pH.  Methods used: Cytological, standard microbiological,  real time PCR, the measurement of vaginal fluid pH. Results: five types  of vaginal microbiota have been revealed, as well as a clear link of pH and the quantitative characteristic of microflora, high inverse correlation with  estradiol content was shown,  and correspondence to the number of gestation complications and the number of inflammatory diseases of the somatic plan was proved. The authors recommend to use pH of the vaginal fluid as an indicator of the state of vaginal biotope in the course of pregnancy.       Keywords: pH of the vaginal secretion, vaginal biotope pregnancy.